African Union Great Green Wall Initiative Strategy and Ten-Year Implementation Framework (2024–2034): Strategic Intervention Axes 2 and 3 - African, Union (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
These posters present Strategic Intervention Axes 2 and 3 of the revised African Union Great Green Wall (GGW) Initiative Strategy and Ten-Year Implementation Framework (2024–2034). The Axes include: 2) Co-designing and delivering pathways toward transformative restoration, resilience and development, and 3) Enhancing the means of implementation for resilient landscape restoration. The Axes are designed to support the achievement of the GGW vision and objectives. Each Axis comprises several intervention areas with specific priority actions, the details of which are included in these posters.